Characterization and Absorption Test of Cellulose from Oil Palm Empty Fruit Bunch for Potential Use in Oil Spill Clean-Up - Afandi N.F.; Tan A.W.-Y.; Mariappan P.; Mahalingam S.; Manap A. (Springer Science and Business Media Deutschland GmbH, 2025)
Empty fruit bunch (EFB) is among the major agricultural waste from the oil palm industry, but its cellulose extract has the potential to clean up hazardous and large-scale oil spills. This research aims to extract cellulose from the oil palm empty fruit bunch fiber and study the water absorption rate of the cellulose. First, extraction processes were conducted using 15% sodium hydroxide (NaOH) and 10% hydrogen peroxide (H2O2). Then, the morphology of empty fruit bunch fiber, crystalline index, and phase identification was characterized using scanning electron microscopy (SEM), and X-Ray diffraction (XRD), respectively. The extracted cellulose was found to have a smaller diameter (8?50m). Alkaline treatment assisted in the removal of hemicellulose, while bleaching aided in the removal of lignin and discoloration. As a result, the extracted cellulose showed a high crystalline index of 30.67%. Moreover, the water absorption rate of the extracted cellulose is calculated, and the maximum water absorption rate of the extracted cellulose was recorded at 269.50%. Hence, this research provides an efficient method for extracting cellulose from oil palm empty fruit bunch fiber and the highest yield of water absorption from the extracted cellulose, primarily used as aerogel in oil spill cleaning. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.